2013
DOI: 10.1371/journal.pone.0057790
|View full text |Cite
|
Sign up to set email alerts
|

Ferricytochrome c Directly Oxidizes Aminoacetone to Methylglyoxal, a Catabolite Accumulated in Carbonyl Stress

Abstract: Age-related diseases are associated with increased production of reactive oxygen and carbonyl species such as methylglyoxal. Aminoacetone, a putative threonine catabolite, is reportedly known to undergo metal-catalyzed oxidation to methylglyoxal, NH4 + ion, and H2O2 coupled with (i) permeabilization of rat liver mitochondria, and (ii) apoptosis of insulin-producing cells. Oxidation of aminoacetone to methylglyoxal is now shown to be accelerated by ferricytochrome c, a reaction initiated by one-electron reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…MG is a highly reactive dicarbonyl aldehyde that is produced mainly during the glycolysis from fructose (through aldolase B catalysis), glyceraldeyde‐3‐P, dihydroxyacetone, and aminoacetone (through semicarbazide‐sensitive amine oxidase or ferricytochrome C catalysis; Fig. ) . Fructose accumulation in models of metabolic syndrome and diet supplementation leads to increased MG formation, which is prevented by aldolase B knockout .…”
Section: Methylglyoxal: Where Can We Find It?mentioning
confidence: 99%
“…MG is a highly reactive dicarbonyl aldehyde that is produced mainly during the glycolysis from fructose (through aldolase B catalysis), glyceraldeyde‐3‐P, dihydroxyacetone, and aminoacetone (through semicarbazide‐sensitive amine oxidase or ferricytochrome C catalysis; Fig. ) . Fructose accumulation in models of metabolic syndrome and diet supplementation leads to increased MG formation, which is prevented by aldolase B knockout .…”
Section: Methylglyoxal: Where Can We Find It?mentioning
confidence: 99%
“…The IBAL/HRP system can also be employed as a model for the molecular elucidation of human "carbonyl stress," since a large collection of metabolites-alkanals, alkenals, α-dicarbonyls, β-ketoacids, α-hydroxyand α-aminoketones, among others, have been shown in vitro, in cell cultures and in experimental animals to be endowed with the potential to produce triplet species, as well as to attach to proteins and nucleic acids (24,46). It should be pointed out that Trp and other redox-active amino acids such as His, Lys, Tyr, Cys and Met can interfere in enzymatic redox cycles through electronic excitation and electron transfer mechanisms.…”
Section: Final Remarksmentioning
confidence: 99%
“…Ferritin --an essential protein responsible for iron storage in soluble and non-toxic form [28] --has been shown to be quite sensitive to harmful • AK radicals and to produce ROS [3,[14][15][16]. It has recently been demonstrated that QH could partially repair oxidative damage inflicted to residues of apoFt or Ft [29].…”
Section: Interaction Of • Ala and • Aa Radicals With Qh Free Or Boundmentioning
confidence: 99%
“…• ALA and• AA radicals have been implicated in pathological processes[3,[14][15][16]. It is therefore of interest to determine whether effective neutralization of • AK radicals by good electrons or hydrogen donors like antioxidants may be possible.…”
mentioning
confidence: 99%